2005
DOI: 10.1107/s1744309105001910
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification, crystallization and preliminary crystallographic analysis of a deblocking aminopeptidase fromPyrococcus horikoshii

Abstract: The deblocking aminopeptidase (DAP) of Pyrococcus horikoshii is a hyperthermophilic exoprotease that cleaves the N-terminal amino acid of peptide substrates with a putative deblocking activity for acylated peptides. DAP has been found to be homologous to a tetrahedral aminopeptidase from the halophilic Haloarcula marismortui. The latter enzyme is a dodecameric complex and has been revealed to be a self-compartmentalized protease whose central cavity harbouring the catalytic site is accessible through several c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Cryoelectron Microscopy Revealed Tetrahedral and Octahedral Hollow Particles-In gel filtration, the PhTET1 protein yields two peaks with apparent molecular masses of 400 and 800 kDa, respectively (22). Analytical ultracentrifugation studies, performed on the partially purified complexes, showed that in addition to a particle with a sedimentation coefficient s 20,w of 15 S, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryoelectron Microscopy Revealed Tetrahedral and Octahedral Hollow Particles-In gel filtration, the PhTET1 protein yields two peaks with apparent molecular masses of 400 and 800 kDa, respectively (22). Analytical ultracentrifugation studies, performed on the partially purified complexes, showed that in addition to a particle with a sedimentation coefficient s 20,w of 15 S, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of the PH0519 protein from P. horikoshii in Escherichia coli, its purification, and the crystallization conditions are described elsewhere (22).…”
Section: Protein Expression Purification and Crystallizationmentioning
confidence: 99%
“…Hexahistidine-tagged proteins were expressed in E. Coli (BL21-Gold[DE3] pLysS; Stratagene) grown in 1 l of either Terrific Broth or selenomethionine medium [ 92 ] in the presence of 50 μg/ml kanamycin, 25 μg/ml chloramphenicol, and in the absence or presence of hemin (12.5 μM; Sigma. Cells were grown at 37 °C to an OD 600 of 1.2, and, following the addition of isopropyl-1-thio-D-galactopyranoside (final concentration 1 mM) to induce expression, the cells were incubated overnight with shaking at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…As described in x2, we used crystallization conditions that led to a new high-resolution form of PhTET1-12s in space group P2 1 with an entire dodecamer in the asymmetric unit (Dura et al, 2010). Surprisingly, the addition of the tris-dipicolinate complex led to the initial F4 1 32 crystal form diffracting at low resolution, that was used for the initial structure determination of PhTET1-12s at 3.09 Å resolution (Porciero et al, 2005;Schoehn et al, 2006).…”
Section: Derivative Crystal Formmentioning
confidence: 99%